Potential intake and risk characterization of heavy metals due to ingestion of soils from parks, playgrounds and picnic areas - Doğan, Nurten. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2010., 2010)
The objectives of this study were to assess urban soil contamination by selected metals (As, Cd, Cr, Cu, Ni, Pb, and Zn) in 24 sites (127 soil samples) in Istanbul, Turkey, investigate relationships between soil contamination and site properties, characterize the risk for critically contaminated sites by taking oral metal bioaccessibility and two soil ingestion scenarios into account. Average metal concentrations were similar in the 17 playgrounds, 4 parks and 3 picnic areas sampled. Five out of 24 sites had systematically higher contamination than background, and measured concentrations generally exceeded Turkish regulatory values. High Cu concentrations in these sites were attributed to the leaching from wood treated with Cu-containing preservatives. Risk characterization for these sites showed that hazard index was below one in both involuntary soil ingestion and soil pica behaviour scenarios for all metals. However, probabilistic carcinogenic risk for As uptake exceeded 1×10-6 in both scenarios. A sensitivity analysis showed that soil ingestion rate was the most important parameter affecting risk estimation. Risk from As uptake for children from soils of parks, playgrounds and picnic areas may be serious, especially if soil pica behaviour is present.|Keywords: children’s health, risk assessment, heavy metals, urban soils, treated wood.
Keywords: Children -- Health and hygiene.; Health risk assessment.; Soils -- Heavy metal content.